Partição de fotoassimilados e aspectos morfoanatômicos em tomateiros mutantes fotomorfogenéticos - de Melo, Hyrandir Cabral; Constantino, Elvis Josefer; Cacho, Renato Corrêa; Carvalho, Rogério Falleiros [UNESP] (My University, 2014)
The aim of this study was to analyze photosynthate partitioning in tomato photomorphogenic mutants at the ends of the vegetative (40 days after emergence [DAE]) and reproductive (69 DAE) stages and to determine its interaction with morphoanatomical aspects. The mutants aurea (au), phytochrome-deficient, high pigment-1 (hp1), light-exaggerated response, were studied along with the non-mutant Micro-Tom (MT) cultivar. The plants were analyzed at 40 and 68 DAE to identify photosynthate source organs and tissues as well as the target organs of remobilized photosynthate during the reproductive stage. The plants were evaluated for their internal and external morphology as well as the percentage of dry mass of their organs. Photosynthate allocation in the hp1 mutant occurred primarily in the roots and leaves, and allocation in the au mutant occurred primarily in fruits. The au mutant showed a high capacity for photosynthate remobilization to fruit during the reproductive stage, and the predominant sources of these remobilized photosynthates were the leaf spongy parenchyma, the root vascular cylinder and the marrow stem.
Photosynthate partitioning and morphoanatomical aspects of photomorphogenic mutants of tomato
Keywords: Au; Hp1; Micro-Tom; Photomorphogenesis; Solanum lycopersicum L